The Road to Grace - Evans, Richard Paul.; Noble, Michael; Encore (Firm : New York); Simon & Schuster Audio (Firm) (New York : Encore/Simon & Schuster Audio, 2012)
In the third part of Richard Paul Evans' Walk series, Alan Christoffersen continues his journey for self-discovery. Determined to walk from his home in Bellevue, Washington all the way to Key West, Florida, Christoffersen meets interesting people along the way who inspire him and change his life for the better.
Keywords: Executives -- Fiction; Life change events -- Fiction; Walking -- Fiction -- United States; Loss (Psychology) -- Fiction; Diaries -- Fiction; Choice (Psychology) -- Fiction; Voyages and travels -- Fiction; Advertising executives -- Fiction; Wives -- Fiction -- Death; Grief -- Fiction; Healing -- Fiction; Audiobooks; Audiobooks